KONSEP PENDIDIKAN UKHUWAH: ANALISA AYAT-AYAT UKHUWAH DALAM AL-QUR’AN - Ikhwan Hadiyyin (Al Qalam, 2016)
The people of Islam in Indonesia at this time split by various problems that arise. For example in a society still found cases conflict and enmities between them. This phenomenon describes that Indonesian society still weak in having the attitude ukhuwah (fraternity), tolerance and equality. Which means, social values written in the Qur’an have not been actualized by Indonesian people whose greatest number of Muslim inhabitant in the world. The research attempt to analyze meaning of the verses ukhuwah in surah Al-Hujurat verse 9-13, surah Ali Imran verse 103, and surah Al-Hasyer verse 8-9 with refer to Tafsir Ibnu Katsir, Tafsir Al Maraghi, Fi Dzilaal al Qur’an, Tafsir Al Furqon and Tafsir Al Azhar. Furthermore, the results of the analysis of the study will be developed into the concept of ukhuwah education that can be applied to Indonesian Muslim society. This research utilize literature qualitative approach which discuss around ukhuwah problems there are in the Qur’an, especially in surah Al Hujurat verse 9-13, surah Ali Imran verse 103, and surah Al Hasyer verse 8-9. The result can be showed that education of ukhuwah according to the interpreters is the Islamic Fraternity. Ukhuwah is branch of faith, while the split is branch of heathenism (Qur’an surah Al Hujurat: 9-13). Ukhuwah sourced of faith and Islam law (syari’ah) as well as Rasulullah SAW manners. The principles are hold fast to the Rope of Allah, engagement, way and His religion (Qur’an surah Ali Imran: 103). It was shown by fraternity between the Anshar very protect the Muhajirin on the Rasulullah (Qur’an surah Al Hasyer: 8-9). While from the development of the verses ukhuwah compiled the Concept of Ukhuwah Education that can be set to the Indonesia Muslim society.Keywords: Brotherhood (Ukhuwah), The Verses of Qur’an, Educational Concept.